An Analysis of Faqihudin's Interpretation of the Houri Verses in the Quran - Nurdin, Asep Sofyan; Hasanudin, Agus Salim (UIN Sunan Gunung Djati Bandung, 2023)
This research examines the interpretations of the verses about heavenly maidens, comparing the perspectives of traditional Islamic scholars with those of feminist interpreters. The objective of this study is to understand the feminist interpreters' perspectives on the verses concerning heavenly maidens in the Quran. This is a qualitative research study that utilizes data from various library sources to provide an analytical description of the verses related to heavenly maidens. Primary sources such as classical Quranic exegesis texts and related works are used as secondary sources. The results of this study reveal several concepts of heavenly maidens in the Quran, with a focus on two specific terms. The first term relates to the phrase â€œazwaju muthahharoh,â€ mentioned in the Quran to signify spouses for the righteous in paradise. The second term is related to â€œHur al-â€˜in,â€ describing the heavenly maidens' physical attributes. These two terms are the primary focus of discussion in this paper because classical Islamic scholars and feminist interpreters offer differing interpretations, leading to varying conclusions regarding the meaning of heavenly maidens. Therefore, through this scholarly paper, we will analyze the feminist interpretation of the Houri verses according to Faqihudin Abdul Kodir.